C‐reactive protein, symptoms and activity of daily living in patients with advanced cancer receiving palliative care. Issue 3 (1st March 2017) - Amano, Koji; Maeda, Isseki; Morita, Tatsuya; Baba, Mika; Miura, Tomofumi; Hama, Takashi; Mori, Ichiro; Nakajima, Nobuhisa; Nishi, Tomohiro; Sakurai, Hiroki; Shimoyama, Satofumi; Shinjo, Takuya; et al.
Abstract: Background: The association between C‐reactive protein (CRP) level, symptoms, and activities of daily living (ADL) in advanced cancer patients is unclear. Methods: Secondary data analysis of a multicenter prospective cohort study consisted of 2426 advanced cancer patients referred to palliative care settings was conducted to examine the cross‐sectional relationships between CRP level, symptoms, and ADL disabilities. Laboratory data, symptoms, ADL, and manual muscle testing (MMT) results were obtained at baseline. Participants were divided into four groups: low (CRP < 1 mg/dl), moderate (1 = < CRP <5 mg/dl), high (5 = < CRP < 10 mg/dl), and very high CRP (10 mg/dl = < CRP). The proportions of eight symptoms, five ADL disabilities, and three categories of MMT according to the CRP groups were tested by chi‐square tests. Multiple‐adjusted odd ratios (ORs) were calculated by using ordinal logistic regression after adjustment for age, gender, site of primary cancer, metastatic disease, performance status, chemotherapy, and setting of care. Results: A total of 1702 patients were analysed. Positive rates of symptoms and ADL disabilities increased with increasing CRP level. In the very high‐CRP group, rates of positivity for anorexia, fatigue, and weight loss were 89.8%, 81.0%, and 79.2%, respectively, and over 70% of patients received assistance for bathing, dressing, going to the toilet, and transfer. The grade of MMT also deteriorated with increasing CRP level. Adjusted ORs for the accumulated symptoms significantly increased with increasing CRP level in the moderate‐CRP, high‐CRP, and very high‐CRP groups [1.6 (95% confidence interval 1.2–2.0), P  < 0.001; 2.5 (1.9–3.2), P  < 0.001; 3.5 (2.7–4.6), P  < 0.001, respectively]. Adjusted ORs for the accumulated ADL disabilities significantly increased in the very high‐CRP groups [2.1 (1.5–2.9), P  < 0.001]. Conclusions: Associations between CRP level, symptoms, and ADL were observed in advanced cancer patients receiving palliative care.